The Impact of STI, N225, and DJI Indices on IHSG with IDX30 Index as the Mediating Variable: A Study of the Indonesia Stock Exchange from 2012 to 2023 - Andi Rante; Hasanudin Hasanudin (International Journal of Economics Development Research (IJEDR), 2024)
Researchers took the title The Effect of STI Index, N225 Index, DJI Index on IHSG with IDX30 Index as an Intervening Variable on the Indonesia Stock Exchange for the 2012-2023 Period. The number of samples is based on the number of companies listed in each index. The analysis method used is quantitative using SEM. The results showed 1) STI has a positive and significant effect on IHSG; 2) N225 has a negative and insignificant effect on IHSG; 3) DJI has a positive and significant influence on IHSG; 4) STI has a positive but not significant effect on IDX30; 5) N225 has a positive but not significant effect on IDX30; 6) DJI has a positive but not significant effect on IDX30; 7) STI has an positive and insignificant effect on IHSG through IDX30; 8) N225 has an negative and insignificant effect on IHSG through IDX30; 9) DJI has an positive and insignificant effect on IHSG through IDX30; 10) IDX30 has a positive and significant effect on IHSG. Keywords: STI, N225, DJI, IDX30 and IHSG.